The origin of the self-appellation Sinti: A historical and linguistic examination - DAPHNE REITINGER (Romani Studies)
The origin of the self-appellation Sinti has been the subject of investigation for well over 200 years. In the wake of the discovery of the Indo-Aryan affiliation of Romani, one of the earliest sources (Biester 1793b) mentioning the term “Sinte” interprets it as der wahre Name (the true name) of all Gypsies and allocates its origin to the province Sindh of the Indian sub-continent (Biester 1793b: 365–6). More recently, Matras (1999; 2019) argued for the term Sinti to be a European borrowing in Romani due to its employment of inflectional patterns characteristic of European loanwords. In this paper, early attestations of this self-appellation with regard to their dialectological inferences are examined and an underlying root sint is ascertained. Via the Middle High German (MHG) etymon sint, in the meaning of “way, road, journey,” and the German collective and appellative suffix -e, the meaning of Sinti is interpreted as “wayfarers” or “those who journey.” This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0.